A Study On Users Perception Towards Google Pay With Special Reference To Puducherry (Journal of Namibian Studies : History Politics Culture, 2023)
The digital payment system is gaining popularity because of the 'Digital India' agenda. Fintech provides user-friendly mobile applications that streamline the payment process. Google Pay operates in the business-to-consumer (B2C) sector within the FinTech market. Google Pay is a top digital wallet in India. Digital wallets facilitate cashless transactions. This research study was undertaken in the Union Territory of Puducherry and specifically in the Puducherry district. The participants are chosen using purposive sampling method. Information for the research has been gathered from 175 participants using standardised questionnaires. The data was analysed using the percentage and frequency analysis. This study paper aims to examine user perceptions of Google Pay and the factors that influence customers to use Google Pay in the Puducherry region.